Harmonization of data from cohort studies– potential challenges and opportunities. (2018) - Dahal, Kamala Adhikari; Patten, Scott; Williamson, Tyler; Patel, Alka; Premji, Shahirose; Tough, Suzanne; Letourneau, Nicole; Giesbrecht, Gerald
No abstract available